Interleukin 17 drives vascular inflammation, endothelial dysfunction, and arterial hypertension in psoriasis-like skin disease - Karbach, Susanne; Croxford, Andrew L.; Oelze, Matthias; Schueler, Rebecca; Minwegen, Daniel; Wegner, Joanna; Koukes, Lija; Yogev, Nir; Nikolaev, Alexei; Reissig, Sonja; Ullmann, Alexander; Knorr, Maike; et al. (Arteriosclerosis, Thrombosis, and Vascular Biology, 2014)
Interleukin (IL)-17A is regarded as an important cytokine to drive psoriasis, an inflammatory skin disease marked by increased cardiovascular mortality. We aimed to test the hypothesis that overproduction of IL-17A in the skin leading to dermal inflammation may systemically cause vascular dysfunction in psoriasis-like skin disease.Conditional overexpression of IL-17A in keratinocytes caused severe psoriasis-like skin inflammation in mice (K14-IL-17A(ind/+) mice), associated with increased reactive oxygen species formation and circulating CD11b(+) inflammatory leukocytes in blood, with endothelial dysfunction, increased systolic blood pressure, left ventricular hypertrophy, and reduced survival compared with controls. In K14-IL-17A(ind/+) mice, immunohistochemistry and flow cytometry revealed increased vascular production of the nitric oxide/superoxide reaction product peroxynitrite and infiltration of the vasculature with myeloperoxidase(+)CD11b(+)GR1(+)F4/80(-) cells accompanied by increased expression of the inducible nitric oxide synthase and the nicotinamide dinucleotide phosphate (NADPH) oxidase, nox2. Neutrophil depletion by anti-GR-1 antibody injections reduced oxidative stress in blood and vessels. Neutralization of tumor necrosis factor-? and IL-6 (both downstream of IL-17A) reduced skin lesions, attenuated oxidative stress in heart and blood, and partially improved endothelial dysfunction in K14-IL-17A(ind/+) mice.Dermal overexpression of IL-17A induces systemic endothelial dysfunction, vascular oxidative stress, arterial hypertension, and increases mortality mainly driven by myeloperoxidase(+)CD11b(+)GR1(+)F4/80(-) inflammatory cells. Depletion of the GR-1(+) immune cells or neutralization of IL-17A downstream cytokines by biologicals attenuates the vascular phenotype in K14-IL-17A(ind/+) mice.
EVALuna2:1859